INFLUENCE OF HEATING REGIMES ON THE STRUCTURE AND MECHANICAL CHARACTERISTICS OF STEEL 60PP - A. I. Gordienko; A. L. Mihluk; V. V. Ivashko; I. I. Vegera (Литьë и металлургия)
Kinetics of phase, structural conversions and change of characteristics depending on the temperature, heating and cooling speed, temperature of steel 60PP drawing is examined.